New Hope for Treating Intervertebral Disc Degeneration: Microsphere-Based Delivery System - Guo, Taowen; Zhang, Xiaobo; Hu, Yicun; Lin, Maoqiang; Zhang, Ruihao; Chen, Xiangyi; Yu, Dechen; Yao, Xin; Wang, Peng; Zhou, Haiyu (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc (IVD) degeneration (IVDD) has been considered the dominant factor in low back pain (LBP), and its etiological mechanisms are complex and not yet fully elucidated. To date, the treatment of IVDD has mainly focused on relieving clinical symptoms and cannot fundamentally solve the problem. Recently, a novel microsphere-based therapeutic strategy holds promise for IVD regeneration and has yielded encouraging results in in vitro experiments and animal models. With excellent injectability, biocompatibility, and biodegradability, this microsphere carrier allows for targeted delivery and controlled release of drugs, gene regulatory sequences, and other bioactive substances and supports cell implantation and directed differentiation, aiming to improve the disease state of IVD at the source. This review discusses the possible mechanisms of IVDD and the limitations of current therapies, focusing on the application of microsphere delivery systems in IVDD, including targeted delivery of active substances and drugs, cellular therapy, and gene therapy, and attempts to provide a new understanding for the treatment of IVDD.